Cholangiolocellular Carcinoma in a Pediatric Patient with Small Duct Sclerosing Cholangitis: A Case Report - Lai, Joanne; Taouli, Bashir; Iyer, Kishore R.; Arnon, Ronen; Thung, Swan N.; Magid, Margret S.; Kerkar, Nanda (Seminars in Liver Disease, 2012)
Although guidelines exist for routine screening for malignancy in adults with primary sclerosing cholangitis, no imaging guidelines exist for the pediatric population. Cholangiolocellular carcinoma is a rare malignant liver tumor that has been found in adults with chronic liver disease. We present a case of cholangiolocarcinoma found in an adolescent boy with small duct sclerosing cholangitis. The diagnosis of small duct sclerosing cholangitis was made at the age of 6 at which time he also had advanced fibrosis histologically, but no evidence of decompensation either clinically or biochemically. Several years after this diagnosis, a small liver lesion was found incidentally on computed tomography scan following a motorcycle accident. This lesion was shown to be stable by magnetic resonance imaging over the course of 2 years. At 15 years of age, magnetic resonance imaging findings changed with features suggestive of malignancy. This led to resection of the lesion. Pathologic examination confirmed the presence of cholangiolocarcinoma, a tumor found primarily in adults with a history of viral hepatitis. To our knowledge, this is the first such report in a pediatric patient.
Keywords: cholangiolocellular carcinoma; small duct sclerosing cholangitis; pediatric